Malnutrition Due to Climate Change in West Sumatra using Structural Equation Modeling with Partial Least Square Approach - Defriani Dwiyanti; Eri Barlian; Abdul Razak; Indang Dewata; Nurhasan Syah; Muchsin Riviwanto; Abdi Iswahyudi Yasril (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
The Climate change exacerbates people’s access to nutritious food and the risk ofmalnutrition, especially for vulnerable groups. West Sumatra’s stunting rate in2022 is above the national average. It is necessary to know the factors that influencemalnutrition. The study uses primary data with a questionnaire on heads of farmerand fisher families in areas vulnerable to climate change in West Sumatra, Indonesia,in 2024. We took a probability proportionate size sample of 305 and analysed it using Structural Equation Modelling with Partial Least Squares. The results showed a malnutritionincidence of 76.4%. Environmental health directly influenced infectious diseases,which in turn affected malnutrition, resulting in a large total effect of 0.113 (11.3%).Environmental health indirectly impacts malnutrition through disease, resulting in asubstantial total effect of 0.309 (30.9%). Adaptation had a direct effect on malnutritionand a large total effect of 0.197 (19.7%). Dietary patterns do not have a significant effect onmalnutrition. Adaptation to change includes reducing the incidence of infectiousdiseases and improving access to sanitation. We need adaptation strategies to enhanceenvironmental health and manage infectious diseases.